Cardiac changes in systemic amyloidosis: visualisation by magnetic resonance imaging. - Cheng, A; Banning, A; Mitchell, A; Neubauer, S; Selvanayagam, J (2006)
Cardiac involvement is a significant cause of morbidity and mortality in patients with amyloidosis. A 73-year old Caucasian woman was admitted to a hospital with increasing dyspnoea. Examination revealed a large left-sided pleural effusion, gross peripheral oedema and a pan-systolic murmur. The electrocardiogram showed low voltage QRS complexes with lateral T wave inversion. Recent angiography had demonstrated normal coronaries. Echocardiography revealed left ventricular hypertrophy and an ejection fraction of 43%. There was a restrictive filling pattern with elevated left-sided filling pressures, left atrial enlargement and mild mitral regurgitation. The right heart was normal with normal filling pressures. The patient was referred for cardiovascular magnetic resonance imaging for investigation of restrictive cardiomyopathy. This case provides a striking demonstration of the characteristic features of cardiac amyloidosis by cardiovascular magnetic resonance imaging - impaired biventricular systolic function, thickened atrioventricular valves, bi-atrial enlargement, increased atrial septal thickness and left ventricular mass, pleural and pericardial effusions, and the most impressive finding of widespread subendocardial hyperenhancement of both ventricles, as well as the inter-atrial and inter-ventricular septa, representing infiltration with amyloid protein. Cardiac involvement with systemic amyloidosis was suspected and confirmed on biopsy. Cardiovascular magnetic resonance imaging should be considered early in the diagnostic work-up of suspected cardiac amyloidosis.